Affecting and Inhibiting Factors for Exclusive Breastfeeding: Systematic Literature Review - Rahmawati, Shinta Alifiana; Utami, Fitria Siswi; Herfanda, Esitra (Muhammadiyah Journal of Midwifery, 2020)
Background: Breastfeeding is one important step for the health and development of infants early in life. An international perspective, breastfeeding is important to increase the chances of a baby's survival. Newborns who are exclusively breastfed have a lower risk of dying from diarrhea and respiratory disease, benefits for cognitive and motor activities, improve the general health of the baby. The aim of the study was to identify affecting and inhibiting factors for exclusive breastfeeding. This study used a Systematic Literature Review (SLR). Searching article from 2013 to 2018, from PubMed, Science Direct, and Proquest databases. Total of 1,115 articles reviewed, 6 articles met the inclusion criteria. Results: Exclusive breastfeeding is very closely related to the support of cultural beliefs, practices, and values as well as social and professional encouragement. Husbands who provide support or motivation for exclusive breastfeeding will certainly give happiness to mothers during breastfeeding. Family support is a supporting factor which in principle is an activity both emotional and psychological given to mothers in providing exclusive breastfeeding. Knowledge is very important in shaping one's actions, one of which is the adequate knowledge of the mother about the importance of exclusive breastfeeding. Support of health workers and the workplace has a positive impact on mothers in providing exclusive breastfeeding. Conclusion: Affecting factors for exclusive breastfeeding was associated with husband, family, health worker, workplace support, cultural traditions, and knowledge. Inhibiting factors for exclusive breastfeeding are internal and external factors.